How Do States Implement Liberal Immigration Policies? Control Signals and Skilled Immigration Reform in Australia. Issue 3 (13th May 2013) - Wright, Chris F.
<x xml:space="preserve">Abstract</x> States often face immigration "control dilemmas" between popular pressures for tighter immigration controls versus economic pressures for more liberal work visa controls. Using a systematic process analysis of recent policy developments in Australia, this article argues that the Howard government's large expansion of "wanted" forms of immigration hinged upon its ability to control "unwanted" forms of immigration. The concept of "control signals" is introduced to account for the government's success in exiting an immigration control dilemma, which allowed it to pursue skilled immigration reforms that would have otherwise proven difficult. A research agenda is established for examining the conditions under which the use of control signals is likely to be successful and for applying the concept to other realms of public policy where states face control dilemmas.